(untitled) (Web of Teachers: Inderscience Research, 2024)
Artificial intelligence has appeared in the world relatively recently, however, it has managed to infiltrate people’s lives with incredible speed. Someone says that neural networks and AI help people by making it easier for them to complete tasks. And someone is afraid of them, because neural networks have already taken away the work of most people. And indeed, many professions that were relevant yesterday are already losing their existence today, or giving up the reins of government to artificial intelligence. Many even say that the profession of a psychologist will soon leave. But is this really the case? Let’s look at it in more detail in the article.